2012
DOI: 10.1097/ajp.0b013e31822af81c
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Parental Concerns About Pain During Childhood Vaccination

Abstract: Contrary to healthcare provider perceptions, the timing of outpatient childhood vaccine appointments allows for the inclusion of pain management interventions. Efforts should now focus on educating healthcare providers and parents about the value of pain management and how to implement evidence-based strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 96 , 97 Two studies reported on the mean waiting time before vaccine injection in the clinics demonstrating feasibility of application of topical anesthetics onsite. In the study by Abuelkheir et al 36 (Saudi Arabia), the mean waiting time before the vaccine injection was 57 minutes (SD=16.7), whereas in the study by Taddio et al 98 (Canada), the mean waiting time reported was 41.6 minutes (SD=28.6). Application of the topical anesthetics while awaiting the appointment is possible if there is sufficient time.…”
Section: Discussionmentioning
confidence: 91%
“… 96 , 97 Two studies reported on the mean waiting time before vaccine injection in the clinics demonstrating feasibility of application of topical anesthetics onsite. In the study by Abuelkheir et al 36 (Saudi Arabia), the mean waiting time before the vaccine injection was 57 minutes (SD=16.7), whereas in the study by Taddio et al 98 (Canada), the mean waiting time reported was 41.6 minutes (SD=28.6). Application of the topical anesthetics while awaiting the appointment is possible if there is sufficient time.…”
Section: Discussionmentioning
confidence: 91%
“…The reasons for vaccine hesitancy are complex and context specific 55 ; however, concerns about pain and fear are well-documented contributors to vaccination noncompliance. 56 , 57 Effective management of vaccine-related pain and needle fear hold promise for improving compliance and health across the lifespan. The HELPinKids&Adults knowledge synthesis is an important step in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…Pain and fear are unfortunate sequelae of vaccine injections. Evidence across varied participants in the process of vaccination, from clinicians 1 to parents of children being vaccinated 2 to the individual undergoing vaccination themselves 3 – 5 unequivocally demonstrates that these adverse events are major challenges to current vaccination practices. Addressing the mandate of the Help ELiminate Pain in Kids & Adults (HELPinKids&Adults) Team to provide a comprehensive update to the 2010 clinical practice guideline on reducing childhood vaccination pain, 6 this meta-analysis served to evaluate process interventions.…”
mentioning
confidence: 99%